-8+3(0)=x

Simple and best practice solution for -8+3(0)=x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for -8+3(0)=x equation:



-8+3(0)=x
We move all terms to the left:
-8+3(0)-(x)=0
We add all the numbers together, and all the variables
-1x+22=0
We move all terms containing x to the left, all other terms to the right
-x=-22
x=-22/-1
x=+22

You can always share this solution

See similar equations:

| 95=-5+33x | | 940200-x=0.1x | | x(-2x+18)^2=0 | | 12/20=m/50 | | 2(x-5)-x=29 | | A-5b=8(3,-1) | | 4(3x-6)=6x-2 | | .66x=-12 | | 19+b=5.7 | | -30+2y=56 | | 2-+4n=-5-3n | | 2+10x=-34-x | | 2+10x=34-x | | 4w-12=-48 | | 4*3^x+1-9^x=27 | | -2(x-6)=14 | | 4*3^x+1-9x=27 | | 9x-1633x=20 | | -3x^2+3-8x=0 | | (x+9)2=9 | | 23=5-t | | ?2(3x?4)?x?3=33 | | t2-7t-8=0 | | 4(2x+1)-2x=-8 | | 0.25x+0.20(100-x)=21 | | 5-8x=12-7x | | H(t)=14+32t-16^2 | | 0.08(x+3000)=3840 | | x^+3x=70 | | (12x-53)+(6x+25)=180 | | 5(3x-3)=16 |

Equations solver categories